2022
DOI: 10.1002/adfm.202112682
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Chalcogenide‐Halides for Stable, Lead‐Free and Defect‐Tolerant Photovoltaics: Computational Screening and Experimental Validation of CuBiSCl2 with Ideal Band Gap

Abstract: Lead halide perovskites have emerged as promising photovoltaic (PV) materials owing to their superior optoelectronic properties. However, they suffer from poor stability and potential toxicity. Here, computational screening with experimental synthesis is combined to explore stable, lead-free, and defect-tolerant PV materials. Heavy cations with lone-pair electrons and mixed anions of chalcogens and halogens as a descriptor for simultaneous realization of defect tolerance and high stability are adopted. Togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The direct character of the band gap of our NCs was corroborated by DFT calculations adopting the HSE functional, which clearly showed the lowest energy interband transition at the Y point (Figure 4), as reported for the isostructural CuBiSCl 2 . 12 The orbital-projected density of states and charge density analyses revealed that the valence band of AgBiSCl 2 is formed by the S-and Cl-p orbitals and by the Ag-d orbitals, whereas the conduction band is dominated by the Bi-p orbital contribution (Figures S12 and S13).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct character of the band gap of our NCs was corroborated by DFT calculations adopting the HSE functional, which clearly showed the lowest energy interband transition at the Y point (Figure 4), as reported for the isostructural CuBiSCl 2 . 12 The orbital-projected density of states and charge density analyses revealed that the valence band of AgBiSCl 2 is formed by the S-and Cl-p orbitals and by the Ag-d orbitals, whereas the conduction band is dominated by the Bi-p orbital contribution (Figures S12 and S13).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, the demand for semiconductors containing low-toxicity elements would suggest to focus on Sn analogues (such as Sn 2 BiS 2 I 3 ) . Another chalcohalide compound that might fulfill these requirements is AgBiSCl 2 , for which solution-phase synthetic methods are lacking so far.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have found that the material remains stable under thermal decomposition at 300 1C and can be stored for 25 days under environmental conditions with a relative humidity of 60%. A prototype of the solar cell was made, proving that the open-circuit voltage is 1.09 V and the PCE is 1.00% 34 (Fig. 6d).…”
Section: One-stage Methodsmentioning
confidence: 93%
“…The black arrows mark the peaks attributed to the compound BiOCl. 34 Copyright 2022, Advanced Functional Materials. (e) I-V plot for single crystals of (CH 3 ) 3 SPbI 3 at room temperature.…”
Section: Two-stage Methodsmentioning
confidence: 99%
“…It has an indirect band gap of 1.57 eV and a high absorption coefficient; however, its 1D nanorod crystal structure and deep trap state are important factors leading to its poor performance . In addition to Bi-based ternary sulfur halides that can be used as light absorbers, quaternary sulfur halides with ABiSX 2 (A is metal cation and X is halogen ion) structure, such as CuBiSCl 2 , AgBiSCl 2 , or MABiSI 2 , possess higher-dimensional (2D/3D) crystal structures which have also been applied as stable light-absorbing materials. However, the PSCs based on ABiSX 2 crystal structures all show unsatisfactory efficiency in the works reported in recent years, and the PCE does not exceed 10%.…”
mentioning
confidence: 99%